PENGARUH KOMBINASI BIOCHAR SABUT PINANG DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG DAUN PADA TANAH ALUVIAL - Dendri, Dendri; Palupi, Tantri; Apindiati, Rita Kurnia (JURNAL AGROTROPIKA, 2025)
Yield of green onion has been declining annually in West Kalimantan where land for cultivating green onion is alluvial soil. This study aims to determine the optimal dosage of a combination of areca husk biochar and NPK fertilizer on the growth and yield of green onion plants in alluvial soil. The research was conducted in Sungai Kakap District, Kubu Raya Regency, West Kalimantan Province, from September to November 2024. A non-factorial Randomized Block Design (RBD) comprised six treatments and four replications: b1 = biochar 2 tons.ha⁻¹ + NPK fertilizer 90% (270 kg.ha⁻¹), b2 = biochar 4 tons.ha⁻¹ + NPK fertilizer 80% (240 kg.ha⁻¹), b3 = biochar 6 tons.ha⁻¹ + NPK fertilizer 70% (210 kg.ha⁻¹), b4 = biochar 8 tons.ha⁻¹ + NPK fertilizer 60% (180 kg.ha⁻¹), b5 = biochar 10 tons.ha⁻¹ + NPK fertilizer 50% (150 kg.ha⁻¹), and b6 = biochar 12 tons.ha⁻¹ + NPK fertilizer 40% (120 kg.ha⁻¹). The observed variables included plant height, number of leaves, number of tillers, fresh weight, root volume, and dry weight. Data obtained from observations were analyzed using Analysis of Variance (ANOVA). If significant differences were found, a DMRT test at a 5% significance level was conducted to determine differences among treatments after obtaining the coefficient of variation (KK). The results showed that the treatment of biochar 10 tons.ha⁻¹ + NPK fertilizer 50% (150 kg.ha⁻¹) was the best dosage, significantly affecting plant height, number of leaves, number of tillers, fresh weight, root volume, and dry weight. Further research is recommended using different doses of areca husk biochar and NPK fertilizer, as well as incorporating additional factors, to evaluate their effects on the growth and yield of green onion plants in different soil types.